The Mitochondrial Unfolded Protein Response as a Non-Oncogene Addiction to Support Adaptation to Stress during Transformation in Cancer and Beyond - Kenny, Timothy C.; Manfredi, Giovanni; Germain, Doris (Frontiers in Oncology, 2017)
Upon accumulation of misfolded proteins in the mitochondria, the mitochondrial unfolded protein response (UPRmt) is activated. This review focuses on the role of this response in cancer. We discuss evidences that during transformation, the UPRmt may play an essential role in the maintenance of the integrity of the mitochondria in face of increased oxidative stress. However, the role of the UPRmt in other diseases is also emerging and is therefore also briefly discussed.